2020
DOI: 10.1021/acsami.0c01113
|View full text |Cite
|
Sign up to set email alerts
|

Boiling Heat Transfer with a Well-Ordered Microporous Architecture

Abstract: Boiling heat transfer through a porous medium offers an attractive combination of enormous liquid–vapor interfacial area and high bubble nucleation site density. In this work, we characterize the boiling performances of porous media by employing the well-ordered and highly interconnected architecture of inverse opals (IOs). The boiling characterization identifies hydrodynamic mechanisms through which structural characteristics affect the boiling performance of metallic microporous architecture by validating em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…Currently, measures to enhance the CHT coefficient include coating hydrophobic layers on the surfaces, [17][18][19] constructing microfin surfaces [20,21] and fabricating surfaces with longitudinal grooves. [22] And the measures to improve BHT coefficient include constructing porous composite layer [23][24][25] and making overall rough surface. [26][27][28][29] However, the vapor-liquid phase change is dynamic from the start of nucleation to the final departure of the vapor bubbles/droplets, and the phase-change heat-transfer system needs to adapt to the conversion of low and high heat flow densities.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, measures to enhance the CHT coefficient include coating hydrophobic layers on the surfaces, [17][18][19] constructing microfin surfaces [20,21] and fabricating surfaces with longitudinal grooves. [22] And the measures to improve BHT coefficient include constructing porous composite layer [23][24][25] and making overall rough surface. [26][27][28][29] However, the vapor-liquid phase change is dynamic from the start of nucleation to the final departure of the vapor bubbles/droplets, and the phase-change heat-transfer system needs to adapt to the conversion of low and high heat flow densities.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembly has continuously attracted interest as a bottom-up nanofabrication technique capable of producing structures with unique properties without the need for manual intervention to guide precise structure formation. , In particular, colloidal self-assembly has been extensively studied and used to fabricate 2D and 3D crystalline arrays of spheres, with diameters ranging from nanometers to tens of microns . These structures, often referred to as opals, have been used, either as-fabricated or as a template, in a wide range of applications including optical coatings and optoelectronics, micro thermo-fluidic systems, electrochemical systems, sensors, , molecular printing, and lithography masks , (Figure ). In these applications, the properties of the resulting structures are dependent on the characteristics of the opal crystal, including its order, porosity, and particle size .…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled opals have been used as-fabricated or as templates for porous materials in a wide range of applications including (a) optical coatings, (b) coatings to enhance boiling heat transfer, , (c) high power density electrodes, (d) molecular and ionic sensors, , (e) molecular printing, and (f) lithography masks. , Depending on the application, the opal properties, such as the colloid size, need to be carefully chosen to optimize the device-level performance.…”
Section: Introductionmentioning
confidence: 99%
“…These structures can generally intensify bubble nucleation and liquid rewetting, and thus improve the boiling performance. For example, the sintering technique was used to produce porous coatings, and pool boiling of water, acetone, and FC-72 , was examined. The electrochemical (electroplating) deposition was also widely employed to generate microporous coatings on which pool boiling of FC-72, , Novec-649, HFE-7200, and water was studied.…”
Section: Introductionmentioning
confidence: 99%
“…Pool boiling of various liquids was experimentally investigated on the surfaces mentioned above, including SES36, HFE-7200, , FC-72, ,,, n-pentane, and water, and on other surfaces. It was found that the boiling performance was considerably enhanced, but micro/nanocomposite structures generally were more favorable than sole micro- or nanostructures concerning the heat transfer coefficient or the critical heat flux. ,, In terms of the enhancement mechanisms, heat transfer enhancement was usually attributed to several aspects, e.g., the increase in active nucleation site density, effective bubble dynamics, and enlarged heat transfer area, but the mechanisms of critical heat flux enhancement varied in various studies, e.g., liquid–vapor competition inside structures, wicking intensification, ,,, and liquid–vapor hydrodynamic instability . To the best of the authors’ knowledge, although so much discussion has been presented concerning the boiling enhancement mechanism, it is still not well understood; there is a lack of detailed and quantitative bubble dynamics regulations by surface structures especially for well-wetting liquids and a controversy over the critical heat flux enhancement mechanism.…”
Section: Introductionmentioning
confidence: 99%